A comparison of different methods for identifying transition steps in the acceleration phase of sprint running - von Lieres und Wilkau, H.; Irwin, G.; Simpson, S.; Elias, M.; Bezodis, I. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Transition steps have previously been identified in the acceleration phase of sprinting. To compare transition steps detected using different measures, three sprinters performed maximal 50 m accelerations from blocks. Sagittal plane kinematics were collected using five 50 Hz cameras while touch-down and toe-off events were identified using a 200 Hz panning camera. Centre of mass height, shin angle and trunk angle at touch-down as well as the step where flight time exceeds contact time were used to detect transitions. Comparable transitions were identified based either on centre of mass height or shin and trunk angles at touch-down. These results provide further knowledge to the way in which the acceleration phase is structured and allows athlete specific biomechanical analysis to aid in the coaching of different sections of the acceleration phase in sprinting.